(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
Dictionaries are the most importantpart of second language acquistion since they are used at every level of language learning. People use them while writing, reading, watching movies or listening to music in the language they are learning. They may choose different dictionaries for different activities since there are different types of dictionaries including monolingual and bilingual dictionaries. We focused on these two types of dictionaries in this research and we examined reasons behind the usage of monolingual and bilingual dictionaries among ESL students at Metu DBE ( Department of Basic English)